In vitro Non-Small Cell Lung Cancer Inhibitory Effect by New Diphenylethane Isolated From Stems and Leaves of Dioscorea oppositifolia L. via ERβ-STAT3 Pathway - Zeng, Mengnan; Ren, Yingjie; Zhang, Beibei; Wang, Shengchao; Liu, Meng; Jia, Jufang; Guo, Pengli; Zhang, Qinqin; Zheng, Xiaoke; Feng, Weisheng (Frontiers in Pharmacology, 2021)
Lung cancer is the most leading cause of cancer mortality throughout the world, of which about 85% cases comprise the non-small cell lung cancer (NSCLC). Estrogen and estrogen receptors are known to be involved in the pathogenesis and development of lung cancer. Dioscorea oppositifolia L. is a traditional Chinese medicine and a nutritious food, and can be an excellent candidate as an anti-cancer agent owing to its estrogen-like effects. However, the stems and leaves of Dioscorea oppositifolia L. are piled up in the field as a waste, causing environmental pollution and waste of resources. In the present study, a new diphenylethane (D1) was isolated from the stems and leaves of Dioscorea oppositifolia L. It was observed that D1 reduced the cell viability, migration, energy metabolism, and induced apoptosis in the A549 cells. Mechanistic studies showed that D1 reduced the STAT3 nuclear localization and downregulated the expression of the STAT3 target genes like Mcl-1, Bcl-xL and MMP-2 that are involved in the cell survival and mobility. Moreover, our results indicated that D1 exhibited estrogenic activities mediated by ERβ, and antagonising ERβ decreased the cytotoxic effect of D1 in A549 cells. In addition, inhibition of the nuclear translocation of STAT3 did not interfere with the binding of D1 and ERβ. However, after antagonizing ERβ, the nuclear translocation of STAT3 increased, thereby demonstrating that STAT3 was the downstream signaling molecule of ERβ. In conclusion, the D1 mediated anti-NSCLC in vitro effects or at least in part can be attributed to the ERβ-STAT3 signaling. Our ﬁndings suggest the role of D1 in treating NSCLC on a molecular level, and can help to improve the comprehensive utilization rate of Dioscorea oppositifolia L.